Modering Financial Fragility In Transition Economies - Jeffrey H. Nilsen; Riccardo Rovelli (Swiss National Bank, Study Center Gerzensee, 1999)
Capital inflows have an enormous importance in the financing of investment in emerging and transition economies. However short-term inflows, intermediated by the banking sector of the emerging economy, may be subject to early withdrawals. We model a situation where such withdrawals are motivated by a change in either the domestic or the foreign fundamentals. We show that, for a given change in fundamentals, a reversal in the capital flows (and hence a currency crisis) is more likely the more risk averse are the foreign investors into the emerging economy. We also show that a policy to tax early withdrawals may discourage capital inflows which are more likely to give rise to fundamental runs, by helping to select relatively less risk averse investors. However, such a policy would have to be fine tuned in order not to discourage all capital inflows.
Keywords: G21; G28; O16; O23; 330; Short-term capital inflows; Currency crisis; Financial Fragility; Chilean tax